Tão diferentes, tão normais: perfis de pessoas com síndrome de Down em João Pessoa - Gomes, Mayara Emmily Chaves (2017)
On this report, entitled "So different, so normal: profiles of people with Down's syndrome in João Pessoa", we show the creation process of a book-report-profile's homonym which contains reports with five people with Down's syndrome. The realization of this one product was the general goal of our Master degree's research, also having as intent to show an alternate approach against the manner the traditional media deals with the theme "Down's syndrome". The way the conventional journalism deals with the subject tends to turn it as secondary and, so, to decrease the importance of the speech of those who have the genetic condition, what was verified after a short summary. After this fact, we saw the need to realize a work which could demonstrate the importance of a speech spot for those who have Down's syndrome and promote their leadership. Said so, to perform the report and the book-report-profile we showed, initially, the theoretic paths focusing in twins with profile and biography, based, mainly, in written of Vilas Boas (2003) and Lima (2002). After this general contribution, we focused on the profile-report's historic aspect, using also as reference Wolfe (2005). Following, we went for understand of the report-book until reach the book-report-profile, following what is defended by Lima (2004) and Belo (2006) and, finally, we declared the motivations to write this type of product, based on a proposal so that there may be transparency on the narrator written, which was proposed by Vilas Boas (2008). The next step, we described the methodological procedures to the report and the product adopting, for this last, the participating observation and the dialog-report combined with the humanized profile with alternatives to collect information, followed by the consideration of Morin (1973) and Medina (1986). Following, we described the step-by-step to realize the book-report-profile "So different, so normal: profiles of people with Down's syndrome in João Pessoa", the structure of the product and the final considerations about the work, where we demonstrate that, if the journalist has sensibility, doing his role of observation, listening and empathetic dialog to people with Down's syndrome, it's possible to their interviewed to be protagonist of their own stories. In the end, we present two appendices, one of them being the book-report-profile.